Cannabidiol Effects on Depressive-like Behavior and Neuroinflammation in Female Rats Exposed to High-Fat Diet and Unpredictable Chronic Mild Stress - Tal Sabbag; Milly Kritman; Irit Akirav (Cells)
Depression and obesity are comorbid conditions linked through shared neuroinflammatory and immune mechanisms. This study examined the effects of chronic cannabidiol (CBD) treatment on behavior and neuroinflammatory gene expression in female rats exposed to a combined model of high-fat diet (HFD) and unpredictable chronic mild stress (UCMS). Rats were subjected to an acute HFD for 2 weeks, followed by 4 weeks of UCMS. CBD (10 mg/kg, i.p.) or vehicle was administered during the final 2 weeks of UCMS. Specifically, mRNA levels of nuclear factor kappa B1 (NF-κB1), tumor necrosis factor alpha (TNF-α), interleukin-1 beta (IL-1β), and IL-6 were measured in the ventromedial prefrontal cortex (vmPFC) and CA1. CBD’s effects varied depending on the type of stressor. It promoted coping behavior, increased locomotion, reduced freezing, and restored UCMS-induced depressive-like behavior in a splash test. In the vmPFC, CBD normalized the HFD- and UCMS-induced increase in il1β, and downregulated nfkb1 and tnfa expression. In the CA1, it normalized stress-induced downregulation in nfkb1 expression. These findings suggest that the efficacy of CBD in modulating both behavior and neuroinflammation is contingent upon the nature of the stress exposure, highlighting its potential as a targeted treatment for stress-related neuropsychiatric disorders in females.